Arendt - Villa, Dana Richard (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Hannah Arendt (1906-1975) was a philosopher and political theorist of astonishing range and originality and one of the leading thinkers of the twentieth century. A former student of Martin Heidegger and Karl Jaspers, she fled Nazi Germany to Paris in 1933, and subsequently escaped from Vichy France to New York in 1941. The Origins of Totalitarianism (1951) made her famous. After visiting professorships at Princeton, Berkeley, and the University of Chicago, she took up a permanent position at the New School in 1967. Renowned for The Human Condition, On Revolution, and The Life of the Mind, she is also known for her brilliant but controversial reporting and analysis of Adolf Eichmann's 1961 trial in Jerusalem-an experience that led to her to coin the phrase "the banality of evil". In this outstanding introduction to Arendt's thought Dana Villa begins with a helpful overview of Arendt's life and intellectual development, before examining and assessing the following important topics: Arendt's analysis of the nature of political evil and the arguments of The Origins of Totalitarianism political freedom and political action and the arguments of On the Human Condition, especially Arendt's return to the ancient Greek polis and her critique of modernity modernity and revolution and Arendt's text On Revolution responsibility and judgment and her reporting of the Eichmann trial Arendt's view of contemplation and the fundamental faculties of mental life Arendt's rich legacy and influence, including her civic republican understanding of freedom and her influence on the Frankfurt School, communitarianism and Marxism. Including a chronology, chapter summaries and suggestions for further reading, this indispensable guide to Arendt's philosophy will also be useful to those in related disciplines such as politics, sociology, history and economics"--
OCLC-licensed vendor bibliographic record.
Keywords: Arendt, Hannah, -- 1906-1975.; PHILOSOPHY / General; PHILOSOPHY / Political; PHILOSOPHY / Religious